"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

Gender inequities in household labor predict lower sexual desire in women partnered with men - Harris, Emily A; Gormezano, Aki M.; van Anders, Sari M. (Archives of Sexual Behavior, 2022)
Low sexual desire in women is usually studied as a problem, one that is located within women. However, other possibilities exist, including known gender inequities related to heteronormative gender roles. In this study, we provide the first test of the theory that heteronormativity is related to low sexual desire in women partnered with men, focusing specifically on inequities in the division of household labor. In two studies with women who were partnered with men and had children (Study 1, N = 677; Study 2, N = 396), performing a large proportion of household labor was associated with significantly lower sexual desire for a partner. Together, the results suggest that this association was mediated by both perceiving the partner as a dependent and perceiving the division of labor as unfair. These results support the heteronormativity theory of low sexual desire in women partnered with men, and show that gender inequities are important, though understudied, contributors to low desire in women partnered with men. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; désir; hétéronormativité; hétérosexisme; projet charge mentale; périodes historiques; santé; sexualité; systèmes d'oppressions; thématiques; travail; travail domestique

Pas ce soir, chéri, j’ai mal à la tête (parce que je fais ton lavage) - Massicolli, Elisabeth (Gazette des femmes, 2022)
Quel est le lien entre la charge mentale et l’épanouissement sexuel des femmes au sein des couples hétérosexuels? On fait le point. Dans le livre Women Who Run With the Wolves, la psychanalyste Clarissa Pinkola Estés écrit : « Il y a cette drôle de chose à propos du nettoyage de la maison… c’est que c’est une tâche qui n’est jamais terminée. C’est la façon parfaite d’empêcher une femme de faire quoi que ce soit d’autre. » L’autrice parle ici du processus créatif : elle affirme que l’art ne peut pas être pratiqué que dans des moments « volés », entre une brassée de lavage et la préparation du souper. Que l’art prend du temps et que l’artiste doit agir avec ses pulsions et, pour y arriver, être en mesure de se reposer.
Keywords: 2000 à aujourd'hui; approches et analyses; charge mentale; conciliation famille-travail; famille; hétérosexisme; projet charge mentale; périodes historiques; ressource en ligne; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; travail domestique

Don’t give mum chocolates for Mother’s Day. Take on more housework, share the mental load and advocate for equality instead - Ruppanner, Léa (The Conversation, 2022)
Keywords: 2000 à aujourd'hui; approches et analyses; care; charge mentale; charge émotionnelle; discipline; hétérosexisme; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible

Le pouvoir de l’amour - EMMA (Emma, 2020)
Salut à toutes et tous, en ces temps confinés j’ai pensé vous mettre à disposition cette histoire inédite de mon tome 3 « La charge émotionnelle ». Je souhaite plein de …
Keywords: approches et analyses; bande-dessinée; care; charge mentale; discipline; discours dominant; femmes*; hétérosexisme; identités LGBTQIA2+; pédagogie; ressource en ligne; santé; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Écoresponsabilité : la nouvelle « charge morale » des femmes - Lemelin, Silvie (2020)
Apparu dans les années 1980, le concept de charge mentale a été popularisé et brillamment illustré par Emma dans sa désormais célèbre bande dessinée Fallait demander [1]. La charge mentale, c’est la charge cognitive invisible que représentent la planification, l’organisation et la gestion de tout ce qui se situe dans la sphère domestique (tâches ménagères, rendez-vous, achats, soins aux enfants, etc.) et qui, chez les couples hétérosexuels[2], échoit généralement aux femmes en plus de leur activité professionnelle. Car les hommes, consciemment ou pas, désignent souvent leur compagne comme la responsable en titre de la logistique familiale. Et ce travail invisible prend énormément de temps et d’énergie psychique ; il génère davantage de stress que l’accomplissement des tâches domestiques comme telles, la charge mentale accompagnant les femmes au boulot et dans toutes leurs activités.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; amériques; approches et analyses; care; charge mentale; environnement; hétérosexisme; inégalités; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; travail invisible

Comment la crise fait-elle ressortir les inégalités de genre ? - Plumauzille, Clyde (2020)
Aides-soignantes, caissières, aides à domicile… ce sont majoritairement des femmes qui se retrouvent en première ligne contre le virus. Comme le rappelle l’historienne Clyde Plumauzille dans ce podcast, ces inégalités ne sont pas nouvelles, la prise en charge d’autrui au sein du foyer ou dans la société étant historiquement dévolue aux femmes.
Performers: _:n2788
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; charge mentale; confinement; covid-19; histoire et politique; hétérosexisme; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; travail; travail domestique; violences; violences conjugales

Travailler la terre et déconstruire l’hétérosexisme: expérimentations écoféministes - Rimlinger, Constance (Travail, genre et sociétés, 2019)
À partir de l’ethnographie de trois lieux ruraux (deux fermes et un gîte) tenus par des femmes lesbiennes et/ou queer qui s’inscrivent dans une critique écologiste et anticapitaliste de la société tout en questionnant les normes de genre et de sexualité, nous interrogerons la signification de ces choix de vie alternatifs au regard de l’identité des actrices et de la manière dont ils enrichissent la compréhension de la constellation des mouvements écoféministes. Nous observerons qu’avec le déplacement de la ville vers la campagne, et du monde salarié vers l’agriculture de subsistance, elles doivent mettre en place de nouvelles stratégies pour lutter contre l’isolement et s’intégrer localement. Simultanément, ce retour à la terre leur offre de nouvelles possibilités d’émancipation, d’engagement et de soutien aux femmes et aux minorités. Le travail agricole, l’engagement féministe et la politisation du quotidien constituent les différentes facettes d’un même projet : celui de chercher une voie plus juste et plus durable pour notre société.
Keywords: 2000 à aujourd'hui; 2010-2019; agriculture; approches et analyses; care; com5170; cours; discipline; environnement; europe; france; hétérosexisme; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; séparatisme lesbien; thématiques; travail; vie rurale; écoféminisme; écologie queer

My butch career: A memoir - Newton, Esther (Duke University Press, 2018)
During her difficult childhood, Esther Newton recalls that she “became an anti-girl, a girl refusenik, caught between genders,” and that her “child body was a strong and capable instrument stuffed into the word ‘girl.’” Later, in early adulthood, as she was on her way to becoming a trailblazing figure in gay and lesbian studies, she “had already chosen higher education over the strongest passion in my life, my love for women, because the two seemed incompatible.” In My Butch Career Newton tells the compelling, disarming, and at times sexy story of her struggle to write, teach, and find love, all while coming to terms with her identity during a particularly intense time of homophobic persecution in the twentieth century. Newton recounts a series of traumas and conflicts, from being molested as a child to her failed attempts to live a “normal,” straight life in high school and college. She discusses being denied tenure at Queens College—despite having written the foundational Mother Camp—and nearly again so at SUNY Purchase. With humor and grace, she describes the influence her father Saul's strong masculinity had on her, her introduction to middle-class gay life, and her love affairs—including one with a well-known abstract painter and another with a French academic she met on a spur-of-the-moment trip to Mexico and with whom she traveled throughout France and Switzerland. By age forty, where Newton's narrative ends, she began to achieve personal and scholarly stability in the company of the first politicized generation of out lesbian and gay scholars with whom she helped create gender and sexuality studies. Affecting and immediate, My Butch Career is a story of a gender outlaw in the making, an invaluable account of a beloved and influential figure in LGBT history, and a powerful reminder of just how recently it has been possible to be an openly queer academic.
Keywords: amériques; approches et analyses; autobiographie; butch; histoire et politique; hétérosexisme; identités LGBTQIA2+; queer; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail; violences; états-unis

The other third shift? Women's emotion work in their sexual relationships. - Fahs, Breanne; Swank, Eric (Feminist Formations, 2016)
Les théories sociologiques du « travail émotionnel » genré ont souvent été examinées en relation avec le travail domestique, le travail du sexe et les emplois qui exigent des soins émotionnels et des « chouchoutages » physiques des clients (par exemple, les coiffeurs, les employés de salons de manucure, les travailleurs médicaux). Les concepts de travail émotionnel ont été beaucoup moins souvent utilisés pour aborder les inégalités dans les relations interpersonnelles privées, en particulier les relations amoureuses hétérosexuelles. Cet article a utilisé une analyse thématique de données qualitatives provenant d'un échantillon communautaire de 20 femmes (âge moyen = 34, écart-type = 13,35) issues d'horizons très divers. Nous avons identifié quatre domaines de travail émotionnel présents dans la vie sexuelle de ces femmes, notamment 1) simuler des orgasmes ; 2) tolérer la douleur sexuelle ; 3) définir la satisfaction sexuelle en fonction du plaisir du partenaire ; et 4) raconter les rapports sexuels qu'elles qualifient de « mauvais rapports sexuels » comme acceptables en raison de la satisfaction du partenaire. Presque toutes les femmes ont mentionné le travail émotionnel dans le cadre de leurs expériences sexuelles actuelles ou passées, car elles ont souvent décrit des rapports sexuels insatisfaisants pour procurer à leurs partenaires (masculins) des sentiments de puissance, d'habileté sexuelle et de domination, en particulier lors de rapports hétérosexuels. Nous discutons des implications pour les éléments sexués de la satisfaction sexuelle, les sentiments à l'égard du sexe que les femmes ne s'attendent pas à ressentir comme agréables, les attentes concernant le mérite et le droit au plaisir sexuel, l'agence sexuelle et les diverses interprétations de la signification de l'orgasme.
Keywords: 2000 à aujourd'hui; approches et analyses; douleurs physiques; hétérosexisme; orgasme; post-structuralisme; projet charge mentale; périodes historiques; santé; sexualité; sexualité des femmes*; systèmes d'oppressions; thématiques; travail; travail émotionnel

Taire ou exposer la diversité sexuelle ? Impacts des normes de genre et de l'hétéronormativité sur les pratiques enseignantes - Richard, Gabrielle (Genre, sexualité & société, 2015)
À partir de 22 entretiens et de 243 questionnaires d’enquête complétés par des enseignants du secondaire du Québec (Canada), cet article interroge l’existence de normes relatives au genre et à l’orientation sexuelle en milieu scolaire. Les résultats suggèrent que les pratiques professionnelles des enseignant(e)s, tant lesbiennes, gais et bisexuels (LGB) qu’hétérosexuel(le)s concernant l’homophobie et la diversité sexuelle sont influencées par ces normes. Trente ans après les premiers travaux sur le vécu des enseignants LGB, la littérature sur le coming out demeure centrale pour comprendre les pratiques professionnelles de ceux-ci ainsi que leurs appréhensions. Based on 22 interviews and 243 survey questionnaires filled out by high school teachers in Québec (Canada), this paper questions the existence of norms relating to gender and sexual orientation in schools. Results suggest that teachers’ professional practices regarding homophobia and sexual diversity are influenced by these norms, whether they identify as heterosexual or as lesbian, gay or bisexual (LGB). Thirty years after the first studies on LGB teachers’ experiences, the coming out literature remains central to the understanding of teachers’ apprehensions and fears, as well as their pedagogical practices.
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; homophobie; hétérosexisme; identités LGBTQIA2+; québec; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire; étude qualitative; étude quantitative

The pedagogical practices of Québec high school teachers relative to sexual diversity - Richard, Gabrielle (Journal of LGBT Youth, 2015)
This article explores the ways in which teachers describe their pedagogical and intervention practices relative to sexual diversity in Québec (Canada). Three variables closely associated with teachers who report inclusive practices emerge: experiential training (based on the experience of a lesbian, gay, or bisexual [LGB] teacher), contact training (from close acquaintance with LGB individuals), and professional training. These factors impact the probability that a teacher will refer to homosexuality, intervene when homophobic incidents occur to deconstruct prejudices, and become the confidant of LGBQ students. Results are discussed based on research on minority teachers and on the roles of straight allies in education.
Number: 2 https://www.researchgate.net/publication/276111985_The_Pedagogical_Practices_of_Quebec_High_School_Teachers_Relative_to_Sexual_Diversity
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; formations; homophobie; hétérosexisme; identités LGBTQIA2+; outils; québec; ressource en ligne; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire

The social construction of sexuality - Seidman, Steven (W.W. Norton & Company, 2015)
In The Social Construction of Sexuality, Steven Seidman investigates the political and social consequences of privileging certain sexual practices and identities while stigmatizing others. Addressing a range of topics from gay and lesbian identities to sex work, Seidman delves into issues of social control that inform popular beliefs and moral standards. The new Third Edition features three new chapters that focus on the changing cultures of intimacy, the promise and perils of cyber intimacies, and youth struggles to negotiate independence and intimate solidarity.– Provided by Publisher.
Section: xv, 301 pages ; 21 cm
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; hétérosexisme; intimité; premier cycle; privilèges; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; travail; travail du sexe

Countering heteronormativity: Exploring the negotiation of butch lesbian identity in the organisational setting - Woodruffe-Burton, Helen; Bairstow, Sam (GENDER IN MANAGEMENT, 2013)
Objectif - Le but de cet article est d'examiner la manière dont les lesbiennes butch gèrent et négocient leur identité sexuelle sur le lieu de travail. Conception/méthodologie/approche - Une étude qualitative utilisant une enquête ethnographique en ligne pour explorer les expériences des lesbiennes en matière d'interprétation de l'identité butch sur le lieu de travail. Les questions éthiques et autres liées à la recherche ethnographique en ligne sont également explorées et discutées. Constatations - La négociation d'identité est une question clé et les lesbiennes font face à une pression constante liée à la gestion de l'identité. Il ne s'agit pas simplement d'une perspective personnelle, mais d'un mécanisme de défense pour contrer la culture hétéronormative au sein des organisations. Les stratégies pour faire face à ces tensions, mises en évidence dans la littérature et reflétées dans cette étude, vont de la « transmission » (se faire passer pour un hétérosexuel) au fait de défier les attentes en matière d'hétéronormativité et de rester fidèle à l'identité individuelle du butch. Implications pratiques - Le document peut aider les professionnels et les dirigeants des ressources humaines à développer des cultures organisationnelles qui intègrent et incluent la différence et contribuent à éviter l'oppression. Il peut également intéresser les chercheurs et les décideurs politiques dans les domaines de la diversité et de l'égalité et des questions relatives aux LGB. Implications sociales - Les résultats présentés ici intéresseront les publics sociaux, y compris les personnes LGBT, les groupes d'activistes et les groupes de soutien. Une meilleure compréhension de la masculinité féminine et de l'identité butch peut contribuer à renforcer la tolérance et l'acceptation. Originalité/valeur - Cette étude répond à des appels en faveur d'une recherche plus approfondie sur les LGBT sur le lieu de travail et dans le contexte organisationnel. Les résultats permettent de mieux comprendre la négociation d'identité dans des conditions d'hétéronormativité. Il est également avancé que cette étude sur les expériences des lesbiennes sur le lieu de travail se positionne comme un site alternatif pour comprendre les organisations, tout en apprenant à proposer un leadership sexospécifique
Keywords: 2000 à aujourd'hui; approches et analyses; butch/femme; hétérosexisme; identité sexuelle; personnes lesbiennes; périodes historiques; systèmes d'oppressions; thématiques; travail

King King théorie - Despentes, Virginie (Grasset, 2006)
J'écris de chez les moches, pour les moches, les frigides, les mal baisées, les imbaisables, toutes les exclues du grand marché à la bonne meuf, aussi bien que pour les hommes qui n'ont pas envie d'être protecteurs, ceux qui voudraient l'être mais ne savent pas s'y prendre, ceux qui ne sont pas ambitieux, ni compétitifs, ni bien membrés. Parce que l'idéal de la femme blanche séduisante qu'on nous brandit tout le temps sous le nez, je crois bien qu'il n'existe pas. V.D.
Keywords: 2000 à aujourd'hui; 2000-2009; anticapitalisme; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; europe; fem1000; fem7000; france; hétérosexisme; identités LGBTQIA2+; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; violences; violences sexistes et sexuelles; études littéraires

Money, myths, and change: the economic lives of lesbians and gay men - Badgett, Mary Virginia Lee (University of Chicago Press, 2001)
How does the standard of living of gay men and lesbians compare with that of heterosexuals? Do homosexuals make financial and family decisions differently? Why are the professional lives of gay men and lesbians dissimilar from those of heterosexuals? Or do they even differ? Have gay people benefited from the recent economic boom? Or have public policies denied them their fair share? Money, Myths, and Change provides new answers to these complex questions. This is the first comprehensive work to explore the economic lives of gays and lesbians in the United States. M. V. Lee Badgett weaves through and debunks common stereotypes about gay privilege, income, and consumer behavior. Studying the ends and means of gay life from an economic perspective, she disproves the assumption that gay men and lesbians are more affluent than heterosexuals, that they inspire discrimination when they come out of the closet, that they consume more conspicuously, that they enjoy a more self-indulgent, even hedonistic lifestyle. Badgett gets to the heart of these misconceptions through an analysis of the crucial issues that affect the livelihood of gay men and lesbians: discrimination in the workplace, denial of health care benefits to domestic partners and children, lack of access to legal institutions such as marriage, the corporate wooing of gay consumer dollars, and the use of gay economic clout to inspire social and political change. Both timely and readable, Money, Myths, and Change stands as a much-needed corrective to the assumptions that inhibit gay economic equality. It is a definitive work that sheds new light on just what it means to be gay or lesbian in the United States.
Section: xii, 302 pages ; 24 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; capitalisme; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; shm4000; systèmes d'oppressions; thématiques; travail; états-unis